2022
DOI: 10.1101/2022.09.01.22279512
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating prospective study registration and result reporting of trials conducted in Canada from 2009-2019

Abstract: Background: Adherence to study registration and reporting best practices are vital to foster evidence-based medicine. Poor adherence to these standards in clinical trials conducted in Canada would be detrimental to patients, researchers, and the public alike. Methods: All registered clinical trials on ClinicalTrials.gov conducted in Canada as of 2009 and completed by 2019 were identified. A cross-sectional analysis of those trials assessed prospective registration, subsequent result reporting in the registry… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Although our results can be explained by the societal need for rapid answers early in the COVID-19 pandemic, we cannot exclude that the pandemic has exposed and magnified pre-existing trends focused on the quantity of publications instead of high-quality research. Supportive of the latter hypothesis is that almost 20 years ago, it was recognised that we perhaps need fewer publications but more of superior quality 48 49…”
Section: Discussionmentioning
confidence: 99%
“…Although our results can be explained by the societal need for rapid answers early in the COVID-19 pandemic, we cannot exclude that the pandemic has exposed and magnified pre-existing trends focused on the quantity of publications instead of high-quality research. Supportive of the latter hypothesis is that almost 20 years ago, it was recognised that we perhaps need fewer publications but more of superior quality 48 49…”
Section: Discussionmentioning
confidence: 99%
“…This practice is required by several organizations and funders internationally. Despite clear mandates for registration, we know this practice is not optimal [ 23 ]. Standardized reporting of trial registration will allow for linkage of trial outputs to the registry and help contribute to the reduction of selective outcome reporting and non-reporting.…”
Section: Methodsmentioning
confidence: 99%
“…gov and completed between 2009 and 2019, found that only 39% of trials had reported results in the registry by early October 2021. 5 Moreover, the problem of non-publication of clinical trials has been documented across many areas of medicine [6][7][8][9][10] and, although more frequent in earlier phase trials, for all phases of clinical trials. 2 Selective reporting of trials has led to less informed patient care, unnecessary harm to patients and a waste of research resources.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also found low compliance with regulatory requirements for timely reporting of clinical trial results within ClinicalTrials.gov and the EU Clinical Trials Register 3 4. A study of clinical trials conducted in Canada, including trials registered in ClinicalTrials.gov and completed between 2009 and 2019, found that only 39% of trials had reported results in the registry by early October 2021 5. Moreover, the problem of non-publication of clinical trials has been documented across many areas of medicine6–10 and, although more frequent in earlier phase trials, for all phases of clinical trials 2.…”
Section: Introductionmentioning
confidence: 99%